Novel mutations in TRPM6 gene associated with primary hypomagnesemia with secondary hypocalcemia. Case report - Papež, Jan; Štarha, Jiří; Slabá, Kateřina; Hubáček, Jaroslav; Pecl, Jakub; Aulická, Štefánia; Urík, Milan; Ceylaner, Serdar; Veselá, Petra; Slabý, Ondřej; Jabandžiev, Petr (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
BACKGROUND: Primary hypomagnesemia with secondary hypocalcemia (HSH) is a rare genetic disorder. Dysfunctional transient receptor potential melastatin 6 causes impaired intestinal absorption of magnesium, leading to low serum levels accompanied by hypocalcemia. Typical signs at initial manifestation are generalized seizures, tetany, and/or muscle spasms. CASE REPORT: We present a 5 w/o female manifesting tonic-clonic seizures. Laboratory tests detected severe hypomagnesemia and hypocalcemia. The molecular genetic analysis revealed two novel mutations within the TRPM6 gene c.3308dupC (p.Pro1104Thrfs*28) (p.P1104Tfs*28) and c.3958C>T (p.Gln1302*) (p.Q1302*) and the patient was successfully treated with Mg supplementation. CONCLUSION: Ion disbalance should be taken into account in the differential diagnosis of infantile seizures. Accurate diagnosis of HSH together with appropriate treatment are crucial to prevent irreversible neurological outcomes.
Keywords: kationtové kanály TRPM; Seizures; Magnesium Deficiency; Renal Tubular Transport, Inborn Errors; Humans; hyperkalciurie; hořčík; hypokalcemie; Hypercalciuria; Female; mutace; Hypocalcemia; záchvaty; lidé; vrozené poruchy tubulárního transportu; ženské pohlaví; TRPM Cation Channels; Mutation; nefrokalcinóza; Magnesium; nedostatek hořčíku; Nephrocalcinosis